2019
DOI: 10.1002/wsb.1015
|View full text |Cite
|
Sign up to set email alerts
|

See what you've been missing: An assessment of Reconyx® PC900 Hyperfire cameras

Abstract: For camera‐trap studies to produce accurate data, cameras should have reliable detection of animals within their field of view. We reviewed 1,503,330 pictures obtained from August–September 2016 and February–March 2017 in North Carolina, USA, using 36 Reconyx® PC900 HyperFire cameras (Reconyx, Holmen, WI, USA). We evaluated factors related to temperature, wind speed, and whether specific detection band(s) and zone(s) may have increased the probability of triggering cameras. We focused on 10 species to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 37 publications
2
18
0
3
Order By: Relevance
“…Cameras frequently missed passing animals, either by failing to trigger, or triggering too slowly (r t and r p , Table 4). These results are similar to those reported by studies using time-lapse images to recognize missed detections in Reconyx brand camera traps [12,39] or CCTV to compare detections of otters [7]. Trigger probability (r t ) appeared to increase with the body mass of the target species (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Cameras frequently missed passing animals, either by failing to trigger, or triggering too slowly (r t and r p , Table 4). These results are similar to those reported by studies using time-lapse images to recognize missed detections in Reconyx brand camera traps [12,39] or CCTV to compare detections of otters [7]. Trigger probability (r t ) appeared to increase with the body mass of the target species (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The number of missed events in camera trap studies is seldom known, and can only be approximated when animal movements are controlled (e.g. Apps and McNutt (2018a) used monitored dog movements to trigger camera traps) or when time-lapse or continuously recording video cameras are used concurrently with camera traps (Glen et al 2013;Newey et al 2015;Jumeau et al 2017;Urbanek et al 2019). Similar to this study, Jumeau et al (2017) found in a study of small animals at wildlife underpasses that Reconyx HC600 camera traps missed 43% of mammal movements recorded from continuous video cameras.…”
Section: Pir Motion-sensor Height Trialsupporting
confidence: 61%
“…Some animals may even avoid camera traps (Meek et al 2016). Additionally, camera traps may not always trigger when an animal moves within the detection zone (Jumeau et al 2017;Urbanek et al 2019;Seidlitz et al 2020), especially when the animal is small (Gompper et al 2006;Damm et al 2010;Rowcliffe et al 2011;Urbanek et al 2019). However, camera traps have many advantages warranting further trials to improve numbat detection probabilities and reduce costs.…”
Section: Discussionmentioning
confidence: 99%